Synthesis of Ca–Si–K–P Composite from Carbide Lime and Rice Husk using Precipitation Method - Reyhan Firmansyah; Ayu Fakhira Yuliananda; Srie Muljani; Luluk Edahwati (UPN Veteran Jatim, 2026)
The development of compositionally multinutrient composite offers a promising pathway to overcome the limitations of conventional fertilizer systems that predominantly focus on N–P–K. In this study, a Ca–Si–K–P composite was synthesized via a controlled precipitation route utilizing carbide lime waste and rice husk ash as sustainable precursors. The effects of precipitation pH (7–11) and calcination temperature (600–1000 °C) on oxide composition and yield were systematically investigated. The results demonstrate that increasing pH from 7 to 11 significantly enhances CaO content, reaching its optimum at pH 9–11, while SiO₂ content decreases by up to 20–30% under highly alkaline conditions due to increased silicate solubility. The K₂O fraction remains relatively low (<10 wt%) across all conditions, primarily due to dissolution losses and thermal volatilization, whereas P₂O₅ exhibits minor variation (<5 wt%) within the studied pH range. Increasing calcination temperature from 600 to 1000 °C leads to a relative increase in SiO₂ content by approximately 10–15%, accompanied by a decrease in CaO fraction and partial loss of K₂O and P₂O₅ at temperatures ≥900 °C. The product yield exceeds 100% due to KOH addition during pH adjustment and shows a decreasing trend with temperature, dropping by approximately 10–20% from 600 to 1000 °C as a result of dehydration and decarbonation processes. Overall, alkaline precipitation conditions (pH 9–11) combined with moderate calcination temperatures (700–800 °C) provide the most favorable balance between compositional homogeneity and yield. These findings highlight the potential of waste-derived resources and precipitation engineering in producing composition controlled Ca–Si–K–P composites, offering significant prospects for application as advanced multinutrient fertilizer precursors.